Impedance characteristics of p-Si /BaxSr1-xTiO3 heterojunction prepared by pulsed laser deposition method - Buniatyan, V.; Davtyan, A.; Begoyan, V.; Dashtoyan, H.
p-Si/BaxSr1-xTiO3 heterojunction properties are investigated by electrochemical impedance spectroscopy method for the first time. The general equivalent circuit model is proposed in circuit description code as: Cf, Rf, Ch,Rh,Rp, where Cf, Rf are the BaxSr1-xTiO3 film conditioned capacitance and resistance, Ch, Rh are the heterojunction depletion layer capacitance and resistance, respectively, Rp is the series resistance. It is stated that the Bode plot curves of the structure in air mostly affected by the depletion layer capacitance of heterojunction Ch(V) .
Keywords: Physics